2005
DOI: 10.1002/pola.21175
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous imaging of the structure and fluorescence of a supramolecular nanostructure formed by the coupling of π‐conjugated polymer chains in the intermolecular interaction

Abstract: We fabricated a micrometer‐long supramolecular chain in which π‐conjugated polyrotaxane was coupled. A new experimental setup was designed and constructed, and the simultaneous direct imaging of the structure and fluorescent function was achieved. Furthermore, we identified the formation of a polymer intertwined network and observed novel fluorescence due to a long‐range interaction via this intertwined network over a distance of 5 μm or more without quenching over 15 min in the near field. © 2005 Wiley Period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…A probe-scan-type atomic force microscope (AFM) (5500AFM, Agilent Technologies, Santa Clara, CA, USA) was used for molecular imaging in the dynamic (tapping) mode with a cantilever (OMCL-AC240TS, Olympus, Tokyo, Japan) having a spring constant of 1.7 N m − 1 and resonance frequency of 70 kHz (typical values). 26 The set point was optimized for the gentle-touch imaging. A specimen for AFM imaging was prepared by a spin-cast method (ca.…”
Section: Methodsmentioning
confidence: 99%
“…A probe-scan-type atomic force microscope (AFM) (5500AFM, Agilent Technologies, Santa Clara, CA, USA) was used for molecular imaging in the dynamic (tapping) mode with a cantilever (OMCL-AC240TS, Olympus, Tokyo, Japan) having a spring constant of 1.7 N m − 1 and resonance frequency of 70 kHz (typical values). 26 The set point was optimized for the gentle-touch imaging. A specimen for AFM imaging was prepared by a spin-cast method (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Some commercial systems also provide software that allows overlay of optical and AFM images. The resulting images exploit the complementary power of fluorescence and AFM imaging, which has been elegantly demonstrated previously [610]. In the aligned and overlaid hybrid images, the AFM image provides the overall conformational properties of the particles in the sample and the positions of the fluorescence signals identify the fluorescently labeled molecules.…”
Section: Introductionmentioning
confidence: 92%
“…In the last five years, there has been increasing interest in the combination of optical approaches and AFM [310], and integrated set-ups are available from different AFM manufacturers. Some commercial systems also provide software that allows overlay of optical and AFM images.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we succeeded in using a total internal reflection fluorescence microscope (TIRFM) to image single-molecule dynamic fluorescence 6,7 and a combination of an AFM and an objective-type TIRFM to simultaneous image the molecular structure and a novel fluorescent phenomenon. 8 In this study, we observed micro-Brownian motion of a single molecule of a chiral helical -conjugated polymer (Figure 1), 4,5,9 which has a structure of a molecular machine, namely a molecular spring, using a high-speed (rapid-scan) AFM at a solid/liquid interface. A high-speed AFM offers outstanding performance for observing the movement of single molecules in aqueous solution at room temperature.…”
mentioning
confidence: 99%